Financial policies management workshop on 30-31 january 2001 - Chartered Institute of Bankers of Nigeria (Lagos : Chartered Institute of Bankers of Nigeria, 2001)
The year 2001 monetary and fiscal policy guidelines recently released by the central bank of Nigeria and the federal government respectfully contain key strategic policies that could jump start the ailing domestic economy. the need to ensure that policy targets are pursued and implemented with the utmost transparency and diligence led the chartered institute of bankers of Nigeria to raise an ensemble of financial system operators and policy makers to help fine tune the implementation of these guidelines for market led growth.
nmn, 23/04/19
Ref.
Keywords: Monetary policies; Finanacial policies